Academic Failure and its Underlying Factors in Medical Students of Urmia University of Medical Sciences - Shahsanam Gheibi; Rahim Mohammad Loo; Seyed Javad Moosavi Vaezi; Zahra Yekta; Reza Pour Ali; Mahnaz Kafili (Kerman University of Medical Sciences, 2011)
Background & Objective : Academic failure in students of Medicine is one of the important educational issues that deserve serious attempts for the identification of its underlying factors and resolving This study was designed to find the rate of academic failure and its underlying causes in Medical students of Urmia University of Medical Science Methods : In this descriptive crosssectional study demographic and academic information of all students of Medicine in clinical setting who had been accepted in Urmia University of Medical Sciences in the academic years of 19992001 were collected from their academic files Data were analyzed through SPSS and using Chisquare and ttests Statistical significant level was considered 005 Results : A total of 176 academic files belonged to the entrant students in 2000 (n=71) 2001 (n=48) and 2002 (n=55) were studied The rate of academic failure was 223% in basic sciences period 07% in preinternship period and 265% in internship period Failure rate in preexternal examination was 1156% and in preinternal examination it was 56% Academic failure showed significant relationship with class nonattendance (p